An unusual presentation of an amoebic liver abscess: the story of an unwanted souvenir. (5th February 2013) - Swaminathan, Vikram; O'Rourke, Joanne; Gupta, Rashmi; Kiire, C F
Abstract : This case was rather unusual with regard to the disease presentation. The patient had non-specific symptoms of weight loss and general malaise, without any history of preceding diarrhoea or dysentery. It is important to be aware of the epidemiology of the disease, and to relate it to patients presenting with symptoms suggestive of amoebiasis. We discuss the recommended investigations and management options for these patients based on the current guidelines/evidence.